Macrophages retain hematopoietic stem cells in the spleen via VCAM-1 - Dutta, Partha; Leuschner, Florian (Journal of experimental medicine, 2015)
Dutta et al. show that targeting VACM-1 expression in splenic macrophages impairs extramedullary hematopoiesis, thus reducing inflammation in mouse ischemic heart and atherosclerotic plaques., Splenic myelopoiesis provides a steady flow of leukocytes to inflamed tissues, and leukocytosis correlates with cardiovascular mortality. Yet regulation of hematopoietic stem cell (HSC) activity in the spleen is incompletely understood. Here, we show that red pulp vascular cell adhesion molecule 1 (VCAM-1)+ macrophages are essential to extramedullary myelopoiesis because these macrophages use the adhesion molecule VCAM-1 to retain HSCs in the spleen. Nanoparticle-enabled in vivo RNAi silencing of the receptor for macrophage colony stimulation factor (M-CSFR) blocked splenic macrophage maturation, reduced splenic VCAM-1 expression and compromised splenic HSC retention. Both, depleting macrophages in CD169 iDTR mice or silencing VCAM-1 in macrophages released HSCs from the spleen. When we silenced either VCAM-1 or M-CSFR in mice with myocardial infarction or in ApoE−/− mice with atherosclerosis, nanoparticle-enabled in vivo RNAi mitigated blood leukocytosis, limited inflammation in the ischemic heart, and reduced myeloid cell numbers in atherosclerotic plaques.